Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2017)
The present issue of Studies in Second Language Learning and Teaching closes the seventh year of the existence of the journal. It is fully warranted to say that 2017 has been yet another successful year for at least three reasons. First, the number of submissions has increased considerably and so has their quality with the effect that SSLLT has become even more established in the field. Second, and closely related to the previous point, the number of downloads of individual papers has been on the rise as well, which must have translated into in the growing number of citations, a metric that is illustrative of the impact the journal is having in the field. Third, we have finally managed to move SSLLT to an electronic platform, with the entire process of submitting, reviewing, processing, editing and proofing papers being handled by the PRESSto publishing system maintained by Adam Mickiewicz University. The transition could not have come at a better time as dealing with the growing influx of submissions was becoming less and less manageable, which was beginning to constitute a threat to the credibility of the journal. I am hopeful that the move to the new platform, with all of its useful functionalities, will not only result it more speedy and efficient processing of the submissions, but will also make it easier for us to find the most suitable reviewers and even further enhance the visibility of SSLLT and its impact in the domain of research in learning and teaching foreign languages.